Pengembangan Soal Terbuka (Open-Ended Problem) pada Mata Pelajaran Matematika Kelas XI MA- Al Hidayah NW Lendang Dami - Nursin Nursin (Lembaga Bale Literasi, 2025)
This aim of study were to produce a valid and good open question test (open-ended problem) in learning mathematics for 8th grade students of JHS. This was a developmental reserach using development model set by McIntire & Miller. The steps in this study included preliminary study, product design, and product development. The result of this study was an open question test (open- ended problem), including test blueprint, 28 items of essay tests, and scoring guide. The validation result showed that the developed tests have a valid category. The developed open questions also have a good characteristic, viewed from the test difficulty and distinguishing power which are in medium category and available received. The generated reliability is 0,72 with the measurement error standard or SEM is 2,376. Based on the field trial result, students’ creative thinking ability just stated on fluently and detail, and student’ mathematics achievement was in positive category. Overall, the study result showed that the developed open questions (open-ended problem) are feasible to use.